ANALISIS DISIPLIN KERJA, PENEMPATAN KARYAWAN DAN PENGAWASAN TERHADAP KINERJA KARYAWAN PADA PT KERETA API INDONESIA DIVRE I SUMATERA UTARA - Khofifah Azhari Lubis; Ahmad Aswan Waruwu (CV. ALIM'SPUBLISHING, 2024)
Performance is an ability that must be possessed by every employee to carry out the duties and responsibilities given by the company to employees. This research aims to examine the influence of work discipline on employee performance, examine the influence of employee placement on employee performance and supervision on employee performance. The population in this study is all employees, number of employees and position at PT. Kereta Api Indonesia (Persero) Divre I North Sumatra and a sample of 50 respondents was obtained. The data collection instrument uses a questionnaire with a Likert scale, each of which has been tested and has met the validity and reliability requirements. Data analysis used multiple linear regression using SPSS 16.0 for Windows software tools. The results of this research show that work discipline has a partially positive and significant effect on employee performance, employee placement has a partially positive and significant effect on employee performance, supervision has a partially positive and significant effect on employee performance. Work discipline, employee placement and supervision simultaneously have a significant effect on employee performance.